Metaverse-Based Demonstrators as an Alternative to Traditional Presentations: Case Fossil-Free Steelmaking Processes - Immonen, Tommi (My University, 2025)
While the definition of a metaverse varies based on the source, all presented definitions generally refer to a similar idea: a virtual world in which users as avatars can interact with each other and the environment. The first metaverses were created already in the early 2000s, which has led to significant advancements in their development until the present day. The latest generation of virtual reality devices has been in development for nearly a decade, because of which the technology is nowadays seen as a revolutionary technology capable of presenting deeply immersive content. Using these two technologies, immersive metaverse experiences capable of significantly improving the understanding received about the presented content can be achieved. The advancements of both metaverse and virtual reality industries have enabled them to develop to a point in which virtual reality metaverses targeted for enterprise usage are feasible. Metaverses naturally enable two-way communication between the users, which is why they can be seen as an improvement over the current business-to-business (B2B) communication methods using only one-way communication methods, such as PDFs, pitches, and brochures. This thesis aims to evaluate the feasibility of metaverses when used as an alternative to traditional presentation methods, which employ one-way communication and static content. In order to conduct the evaluation, a standalone metaverse experience using virtual reality is developed as a prototype, and then tested with user testing. The test users are linked with the maritime industry being either maritime professionals, or researchers working in the industry. The analysis of the test results clearly showed the suggested potential of enterprise-targeted metaverses in practice, highlighting their feasibility as an alternative presentation method. Based on the results, showcasing complex topics with immersive and gamified metaverse experiences using virtual reality devices can significantly help to make them more understandable and user-friendly. This correlates as a result to the upcoming fundamental transformation in B2B communication identified by earlier research.
Keywords: Virtual reality, Metaverse, Steelmaking, Marketing, Communication, Sustainability, Process visualization